Pemberdayaan Masyarakat Dalam Pencegahan dan Penanganan Nyeri Muskuloskeletal dengan Akupunktur Di Lingkungan RW 003 Joho Kidul, Kel. Giriwono Kec.Wonogiri Kab.Wonogiri - Purwanto; Yatmihatun, Sri Yatmihatun,; Sasmita, Hanum (Education and Talent Development Center of Indonesia, 2025)
Musculoskeletal disorders can occur in various levels, ranging from mild to severe. These musculoskeletal disorders usually occur due to work factors or conditions in the workplace such as improper posture, static, and repetitive activities, and can also come from physical exposure such as temperature and vibration. Musculo Skeletal Diseases (MSDs) is a group term for several diseases and injuries to the muscles, tendons, ligaments, joints, and bones. MSDs can affect the back, cervical area, and upper and lower extremities, resulting in pain and disability. Data obtained from the Head of RW 003 Joho Kidul Environment, Giriwono Village, Wonogiri, stated that many residents of Joho Kidul Environment have complaints of musculoskeletal pain such as shoulder pain, back pain, knee pain, and other pain. This can be caused by a lack of knowledge about musculoskeletal pain and efforts to treat it independently. Counseling is needed to increase knowledge about musculoskeletal pain and independent treatment efforts, as well as the need for appropriate health service facilities to help reduce musculoskeletal pain complaints in residents in order to improve quality of life and work productivity. Results: the presence of participants during 1 activity was 85 participants. The gender of participants/residents in community service was 34 men and 51 women. The average age of participants was 56 years, average weight 59 kg, average height 155 cm, according to BMI, 21% of participants were overweight and 17% were obese. As many as 30% of participants had diabetes (GDP> 125), 26% of male participants suffered from high uric acid (> 7.0 mg / dL), 37% of female participants suffered from high uric acid (> 6.0 mg / dL). There were 36 participants who underwent acupuncture therapy with complaints of musculoskeletal pain. Conclusion: Community service with counseling and self-empowerment as well as acupuncture services for musculoskeletal pain sufferers can increase knowledge about the causes and self-prevention efforts and can help serve musculoskeletal pain sufferers with acupuncture therapy for residents of RW 003 Joho Kidul Environment, Giriwono Village, Wonogiri